Crafting Consumer Experiences: The Psychology of Retail Interior Design - Kanak Agrawal; Deepti Pande Rana (International Journal of Architectural Design and Planning, 2024)
The psychology of retail interior design and its influence on consumer behaviour. Drawing upon theories from environmental psychology, consumer behaviour, and retail management, the study investigates how design elements such as colour, lighting, spatial layout, and sensory experiences shape consumer perceptions, emotions, and decision-making processes in retail environments. A comprehensive review of existing literature provides insights into established theories and previous research findings related to retail interior design and consumer behaviour. Through a meticulous examination of design elements such as color schemes, lighting arrangements, spatial configurations, and sensory stimuli, it unravels the intricate dance between these elements and consumer perceptions, emotions, and decision-making processes within retail environments. A thorough review of existing literature serves as a compass, guiding us through established theories and prior research findings in the domain of retail interior design and consumer behaviour. Employing a mixed-methods approach, this research marries the qualitative with the quantitative, blending insights from both consumers and retail professionals. The research employs a mixed-methods approach, combining qualitative and quantitative methods to gather data from both consumers and retail professionals. Qualitative interviews and observational studies offer rich insights into consumer experiences and preferences, while quantitative surveys provide empirical evidence on the impact of design elements on consumer behaviour. The study examines the role of emotional engagement, brand identity, sensory stimulation, and technological integration in creating engaging and memorable retail experiences.
Keywords: Brand loyalty; Case Studies; Retail interior design; ambiance; colour psychology; consumer behavior; customer engagement; design strategies; empirical research; psychology; retail experience; sensory marketing; spatial layout